2016
DOI: 10.1016/j.jinf.2016.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of human bocavirus among children with severe acute respiratory infection in China

Abstract: We described some new characteristics in the epidemiology of HBoV among children with SARI, these data will significantly expand the current knowledge of HBoV epidemic and genomic characterization among children with SARI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
4
7
1
Order By: Relevance
“…It may be that HCoV infections occur as biennial outbreaks in Shanghai [16,[34][35][36][37]. Previous studies have shown that, although HBoV infections occur throughout the year, they are most evident during the winter and spring months [6,38,39]. In contrast, we found that HBoV infections were most common during the summer months in Beijing and Shanghai.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…It may be that HCoV infections occur as biennial outbreaks in Shanghai [16,[34][35][36][37]. Previous studies have shown that, although HBoV infections occur throughout the year, they are most evident during the winter and spring months [6,38,39]. In contrast, we found that HBoV infections were most common during the summer months in Beijing and Shanghai.…”
Section: Discussioncontrasting
confidence: 67%
“…The second round consisted of 94°C for 5 min; then 94°C for 40 s, 55°C for 40 s, and 72°C for 40 s for 25 cycles; and then 72°C for 5 min. HBoV was detected using a nested PCR method as described previously [6]. The nested PCR programs were performed in two cycles as follows.…”
Section: Detection Of Respiratory Viruses By Reverse Transcription Pomentioning
confidence: 99%
See 1 more Smart Citation
“…An additional indicator of different reactions to viruses already in early life might be the surprisingly high number of hBoV detection in our CF cohort. As hBoV is a relatively newly discovered virus, with an unknown role in lung disease, but a probable role in ARTIs,40 further studies are needed for the interpretation of this finding 41…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Recent articles in this journal have highlighted the role of bocavirus and rhinovirus in potentially severe pneumonia in adults and younger children. 3,4 However co-infection with both viruses was very rare among adults. A previous study reported a 16-month child who was infected by HBoV1 and also showed presence of HRV, developed severe pneumonia.…”
Section: Metagenomic Analysis Identified Co-infection With Human Rhinmentioning
confidence: 99%